2000
DOI: 10.2134/jeq2000.00472425002900050016x
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Sorption by Low Organic Carbon Sediments: A Screening for Seven Herbicides

Abstract: The sorption of seven pesticides in 10 Danish aquifer sediments has been studied. These sediments all have a total organic carbon (TOC) content below 1 g kg−1, and include carbonate‐bearing and carbonate‐free Quatenary sand deposits and a Cretaceous chalk aquifer. Batch experiments were carried out with metamitron, atrazine, isoproturon, mecoprop, 2,4‐D, bentazone, and metsulfuron‐methyl at an initial pesticide concentration of 0.25 mg L−1 in ground water. Generally, the sorption decreases in the order: metami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 0 publications
3
29
0
3
Order By: Relevance
“…Stock solutions of 131 14 C-labeled pesticide was prepared with 14 C-labelled pesticides in sterile filtered MilliQ water 132 ). The sediment samples were crushed (only limestone), freeze-dried and 133 sieved (<2 mm) (Madsen et al, 2000). The investigations were carried out in glass tubes (10 134 mL) with Teflon caps at 10°C in the dark and previous tests excluded adsorption on those 135 materials (Madsen et al, 2000).…”
Section: Sorption Investigations 129mentioning
confidence: 99%
See 1 more Smart Citation
“…Stock solutions of 131 14 C-labeled pesticide was prepared with 14 C-labelled pesticides in sterile filtered MilliQ water 132 ). The sediment samples were crushed (only limestone), freeze-dried and 133 sieved (<2 mm) (Madsen et al, 2000). The investigations were carried out in glass tubes (10 134 mL) with Teflon caps at 10°C in the dark and previous tests excluded adsorption on those 135 materials (Madsen et al, 2000).…”
Section: Sorption Investigations 129mentioning
confidence: 99%
“…The sediment samples were crushed (only limestone), freeze-dried and 133 sieved (<2 mm) (Madsen et al, 2000). The investigations were carried out in glass tubes (10 134 mL) with Teflon caps at 10°C in the dark and previous tests excluded adsorption on those 135 materials (Madsen et al, 2000). The water from the Brévilles Spring in the catchment was 136 used as equilibrium liquid in the investigations as representative for the groundwater after 137 treatment with activated carbon to remove pesticides and sterile filtering.…”
Section: Sorption Investigations 129mentioning
confidence: 99%
“…The carbon content of both the soil and the soil solution is expected to have a significant effect on diuron transport since sorption is considered a key process in attenuation (Madsen et al, 2000). The relative proportions of solid phase organic matter and dissolved organic matter effectively compete for hydrophobic organic molecules.…”
Section: Dissolved and Solid Phase Organic Carbonmentioning
confidence: 99%
“…Soil organic matter plays a critical role in atrazine adsorption (Shea, 1989). Sorption of atrazine is high at pH ≤ 6.7 when compared with sorption at higher pH levels greater than 7.4 (Madsen et al, 2000). Clay et al (1995) reported that a combination of ammonia fertilizer and higher soil pH level increased atrazine movement through the soil.…”
Section: Introductionmentioning
confidence: 99%